Crossing Treeline: Bacterioplankton Communities of Alpine and Subalpine Rocky Mountain Lakes - Vincent, Kim; Holland-Moritz, Hannah; Solon, Adam J.; Gendron, Eli M. S.; Schmidt, Steven K. (Frontiers in Microbiology, 2022)
Treeline ecotones mark a dramatic transition in terrestrial communities within mountain environments. From the aboveground vegetation to the belowground microbes, biotic communities differ between the highly divergent alpine (above treeline) and subalpine (below treeline) ecosystems. Yet, much less is known about the partitioning of aquatic communities across treeline. Our goal was to better understand the composition of bacterioplankton communities of alpine and subalpine lakes and identify potential factors that may be driving differences. To do so, we examined bacterial community composition (using 16S rDNA sequencing) of sixteen lakes in the Southern Rocky Mountain ecoregion of Rocky Mountain National Park in Colorado and in the Snowy Mountain range of southern Wyoming. Additionally, we characterized a suite of abiotic factors to gain an understanding of what factors may be contributing to community dissimilarity. Springtime snowmelt brings the flushing of mountain watersheds that connects terrestrial and aquatic ecosystems. This hydrologic connectivity declines precipitously throughout the summer. To capture potential changes to the lake bacterial community composition caused by terrestrial inflow, we included two time points with differing hydrologic connectivity. As hypothesized, bacterial communities differed across treeline on the early season visit during high connectivity with the terrestrial environment. We additionally found several factors correlated to the community dissimilarity: dissolved organic carbon, pH, chlorophyll-a, and total dissolved nitrogen. Interestingly, and contrary to our original hypothesis, communities no longer differed across treeline by the end of the summer. While the mechanisms for these patterns are yet to be determined, they correlate with the timing of increased hydrologic connections with the terrestrial environment in the early summer. We offer several potential scenarios, including both biotic and abiotic factors, that could lead to the patterns we observed. Connectivity between lakes and their surrounding environment mean that changes to the terrestrial environment can alter the biotic community within the lake. Our changing environment is predicted to bring changes to precipitation, which can alter the flushing of solutes, nutrients, and terrestrial microbes into lakes. Preserving the biotic communities of high elevation lakes relies on a better understanding of these unique communities and what might drive their compositional patterns.